Validasi Model Bisnis Pada Usaha Mikro Bidang Pertanian (Studi Kasus: Mulyadi Strawberry) - Mulyadi, Muhammad Rafli Ilham; Ghina, Astri (eProceedings of Management, 2025)
This study aims to validate the business model of a micro enterprise in the agricultural sector, specificallyMulyadi Strawberry, by testing the nine blocks of the Business Model Canvas. Using a qualitative case studyapproach, data were collected through in-depth interviews with 19 informants, including the owner, customers,potential customers, and partners. The findings indicate that 15 risky assumptions in the Business Model Canvasfocusing on consumer desirability, feasibility, and viability that need to be innovated, experimented with, andvalidated. Based on the research, several practical suggestions are also formulated for Mulyadi Strawberry toconsider for future business development.Keywords: Business Model Canvas, Product Development. Innovation, Business Idea Testing, BusinessModel Validation